Characterisation and use of a functional Gadd45g bacterial artificial chromosome. Issue 1 (December 2018) - Warr, Nick; May, Joel; Teboul, Lydia; Suzuki, Toru; Asami, Maki; Perry, Anthony; Wells, Sara; Greenfield, Andy
Abstract Bacterial artificial chromosomes (BACs) offer a means of manipulating gene expression and tagging gene products in the mammalian genome without the need to alter endogenous gene structure and risk deleterious phenotypic consequences. However, for a BAC clone to be useful for such purposes it must be shown to contain all the regulatory elements required for normal gene expression and allow phenotypic rescue in the absence of an endogenous gene. Here, we report identification of a functional BAC containingGadd45g, a gene implicated in DNA repair, DNA demethylation and testis determination in mice and exhibiting a broad pattern of embryonic expression. Mouse fetuses lacking the endogenousGadd45g gene undergo normal testis development in the presence of theGadd45g BAC transgene. Moreover, a survey of embryonicGadd45g expression from the BAC reveals that all reported sites of expression are maintained. This functional BAC can now be used for subsequent manipulation of theGadd45g gene with the confidence that regulatory elements required for embryonic expression, including testis determination, are present. We describe the generation and characterisation of aGadd45g -mCherry fluorescent reporter exhibiting strong expression in developing gonads and neural tissue, recapitulating endogenous gene expression, as evidence of this.